Self-identification of the lyrical subject in Russian poetry (a draft typology) (ENTHYMEMA, 2014)
The end goal of this paper is to shed light on the changes in the lyrical subject self-identification logics that were characteristic of Russian poetry of the ‘modernist’ era. We are going to focus our attention exclusively on the poems with a lexically expressed I, which build the nucleus of the poetic fraction of literary texts and allow to get a clear idea about the mechanism of self-naming that we regard as fundamental for self-identification of the lyrical I.The paper discriminates between the two methods of lyrical subject identification/self-identification: referring and attributing. Based on this, we suggest determining four basic functional incarnations of the lyrical subject in Russian poetry of the 18th–19th centuries, which are in part terminological reconsiderations of the conventional Russian philology categories. These incarnations are: 1) ‘anonymous’ lyrical I referring directly to the real author; 2) lyrical I referring to the author through the prism of in-text heteronymic or metonymic transcoding; 2) lyrical character (lyrical hero) referring to the author through the prism of metaphoric transcoding; 3) role character (role hero) with zero reference to the author.The revolution that affected the strategies of lyrical self-identification in Russian poetry of the Silver Age manifested itself in some fundamental shifts. First of all, kaleidoscopic multiplication of lyrical I’s, both through the lyrics of specific poets and even within individual poems. Second, blurred boundaries between different incarnations of the lyrical subject that had been more or less clearly contrasted in poetry of the 19th century. Third, theatralization and problematization (to the extent of open conflicts) of the relationship between the author and his/her lyrical ‘doubles’.